Features of the Regulation of Stages of Crime in the New Criminal Code of the Republic of Armenia - Gabuzyan, Ara (Bulletin of Yerevan University C: Jurisprudence, 2022)
The article discusses the novelties that are present in the new Criminal Code of the Republic of Armenia regarding the stages of crime. The author reveals the content of these novelties and states that they are more justified than the regulations of the current code.